The Importance of Premarital and Preconception Knowledge - Puteri, Mahfuzhah Deswita; Amalia, Rizki (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2024)
The term "premarital and preconception care" describes the actions women can take both before and in between pregnancies to improve their chances of becoming mothers and having healthy children. Worldwide, millions of women lack access to sufficient and high-quality prenatal, pregnancy, and delivery services. Improving mother and child health will therefore be greatly aided by filling in this large informational vacuum and providing the required resources. The four couples who visited the Sungai Andai Health Center were the activity's targets. Using lecture and question-and-answer formats, community service projects involve educating people on the value of knowledge acquisition prior to marriage and motherhood. Powerpoint presentations and pre-wedding and preconception pamphlets were the medium employed. Questions and answers concerning the significance of information before to marriage and pregnancy were also addressed in the previous session. Based on the findings of the pre- and post-tests, four pairs of prospective husband and wife had increased knowledge.